(untitled) (Kinesiology, 2022)
In order to maintain physical fitness during the COVID-19 quarantine, we designed a short-term intervention with one body-weight exercise – burpees. Thus, the aim of this study was to understand level of feasibility and potential benefits of our protocol to different variables in young adults during the COVID-19 quarantine. An online 4-week intervention was administered to 13 young adults (age 22.5±1.39 years, weight 71.8±10.1 kg). The main phase of each session consisted of burpees, a calisthenics body-weight exercises. The training was administered daily. Data regarding quality of life (QoL), body composition, posture, heart rate variability (HRV), cardiovascular health, and strength were collected before and after the intervention period. Participants’ QoL significantly increased after four weeks (p=.025). Also, participants’ strength improved, assessed by the push-up test (p=.017). Systolic blood pressure showed no difference between the pre- and post-measures, while a significant reduction was found in diastolic blood pressure. The HRV assessment showed increased mean RR (p=.005) and RMSSD (p=.014) and decreased mean HR (p=.004) (in the time domain). For the frequency-domain variables, no significant difference was found. No significant changes were noted in body composition, posture, handgrip strength and countermovement squat jump height. Our preliminary results suggest that the 4-week daily online burpees intervention is a feasible method that could improve QoL, upper body strength and HRV in young adults. This non-time-consuming approach could be easily administered to promote healthy living and counteract physical inactivity during COVID-19 restrictions thanks to its feasibility, short duration, and low cost. Key words: Exercise, Coronavirus, Internet-Based Intervention, Health Promotion